Traditional Art of Cupak Gerantang: Between Cultural Preservation and Tourism Development in West Nusa Tenggara - Mawardi, Taufik; Wangi, Baiq Larre Ginggit Sekar; Muharis Muharis; Kukuh, Lalu Guruh Virgiawan Dwi; Rahman, Basuki (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the potential of the traditional performing art Cupak Gurantang in supporting cultural tourism in West Nusa Tenggara (NTB), Indonesia. Cupak Gurantang is a distinctive folk theater from Lombok that conveys moral and social values through the conflict between Cupak, a cunning character, and Gerantang, an honest one. Through this narrative, the performance functions not only as entertainment but also as a medium for moral education within the community. The study employs a descriptive qualitative approach using interviews, observations, documentation, and literature review as data collection methods. Analysis is conducted through a SWOT method and a participatory approach to explore the cultural functions, preservation challenges, and development strategies. The findings indicate that Cupak Gurantang plays a significant role in preserving local cultural identity and strengthening moral values among society. However, several challenges persist, including limited regeneration of young performers, financial constraints, and the marginalization of traditional arts within a tourism sector that tends to prioritize natural attractions. The study recommends community empowerment, youth training, innovative performance presentations, and the use of digital promotion and integration into cultural tourism packages. With these strategies, Cupak Gurantang holds substantial potential to become a sustainable cultural tourism attraction in West Nusa Tenggara.